Macroeconomic effects of a government overdraft on its central bank account - Tarron Khemraj (Levy Economics Institute of Bard College, 2024)
The Guyana government, from 2015 to 2021, accumulated a large overdraft on its central bank account. It owed this overdraft to a binding debt ceiling limit and fractious political environment that prevented an increase in the ceiling, allowing for the auctioning of Treasury bills to create the liquidity reflux necessary to refill the account. This paper studies the macroeconomic effects of reflux (one-sided sales of Treasury bills) and broken or incomplete reflux (base money expansion) by focusing on domestic inflation, the foreign exchange (FX) rate, and the quantity of FX traded in the local market. The empirical results suggest that the inflation rate is largely driven by foreign price and oil shocks. Nevertheless, the broken reflux adversely affected the local FX market by increasing the demand for foreign currencies, marginally depreciating the exchange rate, and slightly increasing the inflation rate. The latter finding has important implications for the enormous post-2020 budget spending since the discovery of offshore oil. However, reflux was found to have a stabilizing effect on the demand for FX and inflation. Granger predictability tests provide strong evidence that the government spends first from its central bank account before reflux occurs. Finally, the paper discusses a few novel institutional features of Guyana which resemble the monetary circuit framework (with government) of neochartalists.
Keywords: B52; E42; E51; E58; F41; H62; 330; neo-chartalism; fiscal-monetary nexus; government account overdraft; inflation; excess liquidity